Pharmacognostical, Phytochemical Screening and Evaluation of Anti-Ulcer Activity of Ethnomedicinal Plant: (Aerial parts of Cynodon dactylon (L) Pers.) - Soma Jana; Vanga Sridhar; Veldandi Ramakrishna; Pingili Mamatha (International Journal of Phytomedicine, 2015)
Cynodon dactylon (L) Pers. (Family: Poaceae) is known to be a sacred tackler in Indian Hindu mythology is offered to Lord Ganesha and one of the 10 auspicious herbs that constitute the group Dasapushpam in Ayurveda. It is an creeping, graceful, enduring grass, abundantly founding in India.The intention of the present study was to investigate the pharmacognostical, preliminary phytochemical studies and anti ulcer activity of n-hexene, chloroform, methanol extracts of cynodon dactylon in wistar albino rats. Pharmacognostical studies including morphology, microscopy, total ash, acid insoluble ash, water insoluble ash, sulphated ash and loss on drying were determined. The preliminary phytochemical studies were performed to determine the various secondary metabolites. Carbohydrates, proteins, flavonoids, saponins, alkaloids were detected. The cynodon dactylon extracts in dose of 200,400 mg/kg body weight (given orally) were investigated for its potential to protect gastric mucosa against indomethacin induced ulcer model. The common parameter like ulcer index, % protection were used for evaluation of anti ulcer activity.The significant anti ulcer activity was found at the dose of 400 mg/kg of methanolic extract. But 200 mg/kg dose was found to be potent comparable with standard drug Pantoprazole.This study provides scientific evidence that aerial portion of cynodon dactylon extracts have potential anti-ulcer effect which could be either cytoprotective action of the drug.